A life both public and private: expressions of individuality in Old English poetry - LaPadula, Brent (2017)
By looking at a representative sample of Old English poetry, this thesis questions the long-held notion that the individual, or personal-self, was not a reality in the western world until the Renaissance. This research makes use of a variety of recent and past methodological approaches to the self, so that we may apply these theories to a study of the individual in Old English literature, and by extension Anglo-Saxon culture more generally. The four-chapter layout showcases how we may approach and answer the question of self in a variety of Old English verse—from elegies and didactic religious, to the heroic. Each study is unique yet complements that which preceeds and follows it, so as to highlight how the study of self is really an inquiry of only seemingly disparate concepts. The outcome of this analysis demonstrates that the individual, or personal self-concept in Anglo-Saxon England was a reality, and consequently challenges past beliefs that the individual is a relatively modern notion. Thus opening the dialogue once more, my research ultimately asks how we may proceed with the question of self in different contexts, historical eras, and eclectic methodological avenues of inquiry, that we may further develop our understanding of one of the most important and ancient questions in humankind’s story.